A Comprehensive Assessment of the Agricultural Extension System in the Philippines: Case Study of LGU Extension in Ubay, Bohol - Efren B. Saz (Philippine Institute for Development Studies (PIDS), 2007)
Using intensive interviews and observations and secondary data, the study looked at a local government agricultural extension service. It situated the context by describing the agroclimatic, social, and economic conditions of the area including its problems, potentials, and prospects. It also took a closer look at two promising industries in the localityrice and mango production. The study further took a closer look at the local government agriculture extension service in terms of the nature of services offered vis a vis the needs of the clientele specially of the two industries in focus. An assessment of the services resources, competencies, adequacy, timeliness, and quality was also done. Lastly, the study looked at knowledge management using a framework suggested by Dalkir and provided suggestions as to how a poorly equipped agriculture extension service provider such as the Ubay LGU may introduce the concept of knowledge management to make the service more effective and responsive to the peculiarities of the area and people.
Keywords: 330; rice industry; knowledge management; Ubay; mango industry; Municipal Agriculture Office; local agriculture extension service; Landwirtschaftliche Entwicklung; Reisanbau; Tropisches Produkt; Agrarpolitik; Öffentliche Einrichtung; Bohol (Provinz); Philippinen